2020
DOI: 10.1186/s12943-020-01237-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 promotes gemcitabine resistance of pancreatic cancer via activating Wnt/β-catenin and autophagy pathway through modulating the miR-619-5p/Pygo2 and miR-619-5p/ATG14 axes

Abstract: Background Pancreatic cancer is one of the most lethal malignancies and has an extremely poor diagnosis and prognosis. The development of resistance to gemcitabine is still a major challenge. The long noncoding RNA PVT1 was reported to be involved in carcinogenesis and chemoresistance; however, the mechanism by which PVT1 regulates the sensitivity of pancreatic cancer to gemcitabine remains poorly understood. Methods The viability of pancreatic cancer cells was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(218 citation statements)
references
References 55 publications
(67 reference statements)
2
216
0
Order By: Relevance
“…Previous evidences have demonstrated that non-coding RNAs, such as miRNAs and lncRNAs, play crucial and complex roles in tumor occurrence and progression. 22 - 24 LncRNAs can regulate mRNA expression by competitively binding to share miRNAs. 25 Increasing studies suggest that the lncRNA-miRNA-mRNA axis is involved in the carcinogenesis of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidences have demonstrated that non-coding RNAs, such as miRNAs and lncRNAs, play crucial and complex roles in tumor occurrence and progression. 22 - 24 LncRNAs can regulate mRNA expression by competitively binding to share miRNAs. 25 Increasing studies suggest that the lncRNA-miRNA-mRNA axis is involved in the carcinogenesis of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, activated autophagy by lncRNA H19, an imprinting lncRNA, contributes to tamoxifen resistance via upregulating Beclin1 expression [ 107 ]. One additional study indicated that lncRNA human plasmacytoma variant translocation 1 (PVT1) induces autophagy through increasing the protein and mRNA levels of Pygo2 and ATG14 and enhances cell resistance to gemcitabine in pancreatic cancer [ 108 ].…”
Section: Mechanisms Of Autophagymentioning
confidence: 99%
“…A relevant study reported that miR-619-5p suppresses proliferative and invasive capacities of colorectal carcinoma cells [42]. A latest report demonstrated that miR-619-5p enhances sensitivity of pancreatic cancer cells to gemcitabine via activating the Wnt/β-catenin signaling pathway [26]. It is concluded that miR-619-5p not only serves as a tumor biomarker, but also a potential therapeutic target for preventing tumor growth and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that miR-619-5p served an anti-cancer role in OSCC cell lines. An earlier study reported that miR-619-5p enhanced the sensitivity of pancreatic cancer to gemcitabine [26]. MiR-619-5p shows a potential influence in chemotherapy resistance.…”
Section: Ivyspringmentioning
confidence: 95%